Optimization of Plant Growth Regulators and Bioreactor Systems for Efficient In Vitro Shoot Multiplication and Elongation of Amorphophallus muelleri Blume - Nur Afni Jayanti; Angelia Krisdanti Nasera Putri; Yosephine Sri Wulan Manuhara; Anjar Tri Wibowo (Universitas Sebelas Maret, 2025)
Porang (Amorphophallus muelleri Blume), an Indonesian endemic species rich in glucomannan, is widely utilized in food industries for its health benefits. However, its traditional vegetative propagation through bulbils produces limited plants, necessitating an efficient in vitro multiplication system. This study aimed to optimize plant growth regulator combinations and bioreactor systems for enhanced shoot induction and elongation of A. muelleri. During the initiation and induction stages, combinations of thidiazuron (TDZ) with benzylaminopurine (BAP) or kinetin at concentrations ranging from 0 to 1.00 mg l⁻¹ were applied to solid MS media and observed for 8 weeks. The combination of TDZ 0.50 mg l⁻¹ + BAP 1.00 mg l⁻¹ produced the fastest shoot induction (32.34±2.52 days), while TDZ 0.75 mg l⁻¹ + BAP 0.75 mg l⁻¹ resulted in the highest shoot number (76.33±22.81 shoots explant⁻¹) and 100% shoot formation. TDZ combined with kinetin had no significant effect on induction parameters. For elongation, shoots induced from TDZ 0.75 mg l⁻¹ + BAP 0.75 mg l⁻¹ medium were cultured in two bioreactor systems: a Temporary Immersion System (TIS) and a Balloon Type Bubble Bioreactor (BTBB). The BTBB significantly outperformed the TIS, yielding 85.2±3.35 shoots explant⁻¹ with an average shoot length of 5.67±1.13 mm after 4 weeks. These results indicate that the synergistic use of TDZ and BAP, combined with the BTBB system, substantially improves in vitro shoot multiplication and elongation of porang, providing a reliable approach for its large-scale propagation and conservation.